ANALISIS KEBTUHAN PELATIH FUTSAL DI KABUPATEN GRESIK TERHADAP PROGRAM LATIHAN BERBASIS DIGITAL - Nafis, M Abd Rohman; Kusuma, I Dewa Made Aryananda Wijaya (Universitas Negeri Surabaya, 2021)
The training program is an important element in performance sports, this is because it becomes a guideline for training instructions so that training can be carried out optimally. The rapid development of technological knowledge must be used as a moment to accelerate the progress of sports, one of which is by switching to digitalization-based training programs in accordance with the existing developments. This study aims to examine and find answers to the level of need for futsal coaches in Gresik Regency for digitalization-based training programs in accordance with the existing developments. This research method is quantitative with a quantitative descriptive approach that describes certain symptoms, phenomena or events. The target of this research is the futsal coaches in Gresik Regency who already have a national futsal coaching license as many as 14 coaches. The data collection instrument used a questionnaire/questionnaire. The data collected from the questionnaire were analyzed using percentages manually. The results showed that the level of need for futsal coaches in Gresik Regency for digitalization-based training programs was 35.7% in the moderate category. This is because the coach is still technologically challenged and there are no special facilities for creating digital-based training programs from the club. Based on the results of this research, the trainer can start implementing a digitalization-based training program in accordance with the development and according to existing conditions to support the success of the process of an exercise.